Acupuncture Treatment Reduces Incidence of Parkinson's Disease in Patients With Depression: A Population-Based Retrospective Cohort Study in Taiwan - Huang, Cheng-Hao; Lin, Mei-Chen; Hsieh, Ching-Liang (Frontiers in Aging Neuroscience, 2020)
Depression is a risk factor for subsequent Parkinson's disease (PD). Some patients with depression undergo acupuncture treatment because of other diseases in Taiwan. Therefore, the present study used data from Taiwan's National Health Insurance Research Database (NHIRD) to investigate the incidence of PD in patients having depression with and without acupuncture treatment. We conducted a retrospective study of a matched cohort of 48,981 patients with newly diagnosed depression between 2000 and 2012 who were selected from the NHIRD. The 1:1 propensity score method was utilized to match an equal number of patients (N = 9,189) in the acupuncture and non-acupuncture cohorts. We employed Cox proportional hazard models to evaluate the risk of PD. The cumulative incidence of PD in both cohorts was estimated using the Kaplan–Meier method, and the difference was examined through a log-rank test. Patients with depression who received acupuncture treatment demonstrated a lower risk of PD [adjusted hazard ratio (aHR) = 0.39, 95% confidence interval = 0.31–0.49] than those who did not undergo acupuncture treatment, after adjusting for age, sex, insurance amount, geographic region, urbanization levels, comorbidities, and drugs. The cumulative incidence of PD was significantly lower in the acupuncture cohort than in the non-acupuncture cohort (log-rank test, p < 0.001). The database did not indicate the severity of depression and acupoints. The results suggest that acupuncture treatment significantly reduced the development of PD in patients with depression; however, a future study should be conducted to provide more objective evidence.